Failure mechanism and predictive model of lithium-ion batteries under extremely high transient impact. (November 2021) - Yu, Da; Ren, Dongsheng; Dai, Keren; Zhang, He; Zhang, Jinming; Yang, Benqiang; Ma, Shaojie; Wang, Xiaofeng; You, Zheng
Highlights: The voltage of lithium-ion batteries under high impact is measured, with a sharp drop and slow rise. The partial short circuit of the separator and the relaxation effect contribute to the impact failure. MI-PNGV model is proposed to simulate the failures under different extreme mechanical conditions. The design guideline is proposed to avoid the mechanic impact failure of lithium-ion batteries. Abstract: With the advantage of high energy density, lithium batteries are widely used in industrial and military applications. However, under the complex conditions of vehicle collision and high-speed flight ammunition, lithium-ion batteries have functional failure, which seriously affects the safety and stability of systems using batteries. In this paper, research on the electric parameter drift of lithium-ion batteries under high impact is carried out through a machete test system, and the experimental phenomena are analyzed theoretically. Based on this, an equivalent circuit model is established to analyze the failure phenomenon and mechanism of lithium-ion batteries under more extreme impact scenarios, which are difficult to test in the laboratory. Finally, the mechanical impact dynamic (MID) model of lithium-ion batteries at the moment of high impact is established, and the influence of separator thickness, elastic modulus and other parameters on the impact resistance of lithium-ion batteries is revealed, which provides a reference for the optimization design of lithium-ion batteries under a high-impact environment.